The evidence and its importance in crimes against public administration - Ibañez Zavala, Nora (2017)
Our current criminal procedure does not offer a legal concept of evidence, only aspects of activity, purpose, assessment and use, less a definition of evidence. For this reason, one must resort to doctrine and jurisprudence in order to know its scope. Despite this, the indiciaia test can contribute greatly in the process, for this it is necessary to know it in order to put it to good use. Such is the case that, in the crimes committed against the Public Administration, the evidence obtained during the investigation carried out by the prosecutor is often not enough, and leaves many loose ends that do not allow clarifying the commission of the criminal act and the participation of the or the authors and others involved, that is where the indiciaia test comes in.